Answer:
p =1
q = 9
Explanation:
f(x) = 2x³ - px² + 2qx + q
(x - 3) is a factor of f(x)
⇒f(3) = 0
2(3)³ - p*3² - 2q*3 +q = 0
2*27 - 9p - 6q + q = 0
54 - 9p - 5q = 0
-9p - 5q = -54 -------------------(I)
(2x - 1) is a factor of f(x)
2x - 1 = 0
2x = 1
![\st x = (1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/4jn7bmpalmln842l5iix0ifpoz51b7frpu.png)
f(1/2) = 0
![2*((1)/(2))^(3)-p*((1)/(2))^(2)-2q*(1)/(2)+q=0\\\\2*(1)/(8)-p*(1)/(4)-q+q = 0\\\\(1)/(4)-(1)/(4)p =0\\\\[Multiply the entire equation by 4]\\\\4*(1)/(4)-4*(1)/(4)p=0\\\\](https://img.qammunity.org/2023/formulas/mathematics/high-school/i12ye1fb187o4qlszcd9biuoxeifovn60k.png)
1 - p = 0
-p = -1
p = 1
Substitute p =1 in equation (I)
-9*1 - 5q = -54
-9 - 5q = -54
-5q = -54 + 9
-5q = -45
q = -45/(-5)
q = 9